2019
DOI: 10.1111/jop.12943
|View full text |Cite
|
Sign up to set email alerts
|

A review of recent advances in histopathological assessment of head and neck squamous cell carcinoma

Abstract: Squamous cell carcinoma (SCC) is the most common non‐cutaneous head and neck (H&N) malignancy. Referrals for suspected SCC are seen by oral and maxillofacial surgery (OMFS) surgeons and represent the bulk of 2‐week wait referrals. The diagnosis and treatment of SCC is heavily influenced by national and international guidelines. The majority of research and funding is directed towards this condition. This has led to continuous changes to update these guidelines. However, there remain areas of controversy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The cause of OSCC is like any other cancer; a DNA mutation that often occurs spontaneously but is increased by chemical, physical, and microbial mutagenic agents. [ 3 4 ] Various studies have shown that the epidemiological pattern of oral and lip cancers is changing. Among them, an increase in the prevalence of SCC, especially among young people, has been shown, which is associated with higher tobacco and alcohol use among young people.…”
Section: Introductionmentioning
confidence: 99%
“…The cause of OSCC is like any other cancer; a DNA mutation that often occurs spontaneously but is increased by chemical, physical, and microbial mutagenic agents. [ 3 4 ] Various studies have shown that the epidemiological pattern of oral and lip cancers is changing. Among them, an increase in the prevalence of SCC, especially among young people, has been shown, which is associated with higher tobacco and alcohol use among young people.…”
Section: Introductionmentioning
confidence: 99%